THE DYNAMICS OF MUSLIM INTERPRETATION OF JIHAD VERSES: Between Morality And Military - Dri Santoso (IAIN Ponorogo, 2022)
The article questions the general assumptions in interpreting the Jihad verses as justifications for intolerant actions among religious organizations and transnational movements in Indonesia. It is due to a misunderstanding of the verses of the Qur'an and the hadith of the Prophet about Jihad without regard to its meaning and historical context. In the use of the Qur'an, especially in the revelation of the first Meccan revelations, the main emphasis is on the meaning of peaceful Jihad as an individual effort for self-improvement. It shows that the verses of Jihad have not connoted military action so far. However, in the second year after the Hijrah, permission for military movement or war was granted when the Muslim community in Medina. The interpretation of the verses of Jihad in the next period changed. The interpretation of Jihad for specific groups as justification for acts of violence contradicts the basic meaning of the verses of Jihad. This shows that the verse of Jihad faces the dynamics of interpretation for a group of Muslims both in terms of justification and contextualization. This article questions the idea that the interpretation of Jihad is inherently a military confrontation rather than a moral struggle. This study also confirms that religious authority influences the dynamics in interpreting religious texts as the interpretation of jihad verses.